Subcritical water hydrolysis for sugar recovery from bakery leftovers: kinetic and thermodynamic analysis - Mohd Thani, Nurfatimah; Mustapa Kamal, Siti Mazlina; Taip, Farah Saleena; Sulaiman, Alifdalino; Omar, Rozita (Springer, 2021)
This study aims to perform kinetic and thermodynamic analysis of subcritical water hydrolysis (SWH) of bakery leftovers. Hydrolysis kinetics of leftover croissants (LC) and leftover doughnuts (LD) into monosaccharides and by-product (hydroxymethylfurfural, HMF), via subcritical water hydrolysis, were studied in temperature range of 100 to 240°C for 6 to 30 minutes and solid loading of 10 (w/v). The monosaccharides yield increased from 100 to 200°C, but it decreased when the temperature further increased from 220–240°C due to degradation of monosaccharides into its by-product (HMF). The activation energy (Ea) monosaccharides degradation was higher than its formation: 104.87 and 88.55 kJ/mol (LC) and 104.69 and 75.72 kJ/mol (LD). The positive values of ΔG# signified that the SWH for sugar recovery from LC and LD is an endergonic reaction.